2010
DOI: 10.3138/jvme.37.1.40
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Veterinary Students Enrolled and Not Enrolled in an Animal-Welfare Course

Abstract: An online survey was conducted to compare 46 veterinary students who previously enrolled in a discussion-based animal-welfare elective with 45 veterinary students who did not take the course. Students were asked a series of questions about their attitudes toward animal welfare and were presented with animal-use scenarios that had not previously been discussed in the elective course: greyhound racing, veal calf production, and the use of genetically engineered mice in research. For each scenario, students' actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
1
10
2
Order By: Relevance
“…The results of this survey indicate that the course had a positive effect on respondents' opinions toward the inclusion of an animal welfare course in the veterinary curriculum. These results are similar to the post-course sentiments of students at other veterinary schools who agreed that an animal welfare course was “challenging and effective” (17) and should be a vital element of the veterinary curriculum (15, 17). The material presented in the course at CSU may have been more intellectually and emotionally engaging than students had expected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of this survey indicate that the course had a positive effect on respondents' opinions toward the inclusion of an animal welfare course in the veterinary curriculum. These results are similar to the post-course sentiments of students at other veterinary schools who agreed that an animal welfare course was “challenging and effective” (17) and should be a vital element of the veterinary curriculum (15, 17). The material presented in the course at CSU may have been more intellectually and emotionally engaging than students had expected.…”
Section: Discussionsupporting
confidence: 80%
“…In the last 20 years, several surveys have been conducted to better understand veterinary students' capacity for empathy toward animal suffering, pain, and overall compromised well-being; their knowledge of welfare issues; and their attitudes toward animal welfare education (1318). Surveys analyzing responses by DVM students enrolled in animal welfare courses have generally found that the courses have effectively challenged students to improve their ability to identify compromised welfare, discuss solutions and encouraged ethical considerations (15, 17). A 2010 study of DVM students revealed that an elective animal welfare course promoted favorable opinions toward the prospective inclusion of such a course in the required curriculum, improved knowledge of welfare evaluation criteria and strategies, and promoted confidence in self-educating about animal welfare topics (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies highlighted a reduced sensitivity of veterinary students to non-human animals and their welfare over the years of their course [ 11 , 13 , 14 ]. Hazel [ 15 ] found that attendance to a course on animal welfare was effective in improving attitudes towards certain animal species, but these positive results are not universally shared [ 5 , 51 ]. Taken together, all of this knowledge suggests that more effort should be devoted in veterinary curricula to indirectly enhance the welfare of farm species to convince students that, in today's livestock farming, it is not just about the survival of the animals, but, above all, it is about the quality of their lives [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the undergraduate veterinary medicine curriculum focuses on the treatment of diseases and the relief of animal suffering (Broom 2005). However, with growing global concern for animal welfare and the reduction of animal use in substance testing and experiments, animal welfare and ethics in animal experimentation have become standard components of the veterinary medicine curriculum (Herzog 2002;Russow 2002;Lord et al 2010).…”
Section: Introductionmentioning
confidence: 99%